QUALITY OF LIFE AND HEALTH OUTCOME ASSESSMENT QUESTIONNAIRES - Sibel Başaran,; Rengin Güzel,; Tunay Sarpel, (Archives of Rheumatology, 2005)
Quality of life (QOL) is an important outcome measure for health condition and the evaluation of treatments. Health related quality of life is the component of overall quality of life that is determined primarly by the person's health and which can be influenced by clinical interventions. The International Classification of Impairment, Disability and Handicap (ICIDH) published by World Health Organisation (WHO) was revised in 2001 as International Classification of Functioning, Disability and Health (ICF). In ICF, the view of "components of health" or "interactions between components" was accepted instead of the old causal view. Since the new ICF framework also defines the personal factors, it can be used to obtain more information about QOL. In this review, ICF framework and frequently used generic and disease spesific questionnaires for evaluating QOL and health outcomes are overviewed.